Not All SLAPs Are Created Equal: A Comparison of Patients with Planned and Incidental SLAP Repair Procedures - Mark C. Dougherty; J. Erik Kulenkamp; Haroutioun Boyajian; Jason L. Koh; Michael J. Lee; Lewis L. Shi (Advances in Orthopedics)
Background. Epidemiological studies have shown a progressive increase in the rate of superior labrum anterior-posterior (SLAP) repair surgery after the year 2000. However, it is not clear whether this is due to increased recognition of isolated SLAP tears or increased SLAP repair performed secondarily during arthroscopy for other purposes. Hypothesis/Purpose. We hypothesized that both isolated SLAP repair and secondary SLAP repair increased with time and that patient age influenced the pathway to SLAP diagnosis and surgery—such that younger patients were more likely to have isolated SLAP repair surgery after being diagnosed in clinic. Study Design. Descriptive epidemiology study. Methods. Data were obtained from the MarketScan database from 2003 to 2013. CPT and ICD-9 codes were used to identify SLAP surgery patients and concomitant procedures. The timing of SLAP diagnosis relative to surgery was used to determine whether the injury was recognized preoperatively. Results. 64,497 SLAP surgery patients were included. Preoperative SLAP diagnosis increased from 17.1% in 2003 to 44.6% in 2013. Patients diagnosed preoperatively were younger and had fewer concomitant procedures. Increasing age and concomitant rotator cuff tear (RCT) repair corresponded to lower odds of preoperative SLAP diagnosis. Discussion. Younger patients were more likely to have their SLAP tear diagnosed prior to surgery. Those diagnosed before surgery had fewer simultaneous procedures during their operations, suggesting that SLAP repair was more likely the primary operation. From 2003 to 2013, SLAP tears were increasingly recognized in the preoperative setting.